1998
DOI: 10.1002/hep.510270114
|View full text |Cite
|
Sign up to set email alerts
|

Right-sided pedunculated hepatocellular carcinoma: A form of adrenal metastasis

Abstract: Pedunculated hepatocellular carcinoma (HCC) or extrahepatic growth of HCC is an uncommon but not rare pathological form, but its genesis is unknown. Right-sided adrenal metastases of HCC that were abutting on or about to fuse with the right hepatic lobe were resected in three patients. The masses seemed to have originated in the para-adrenal tissue, leaving the adrenal gland intact. They were partially supplied by the hepatic artery as well as by the suprarenal artery. Four cases of autopsied pedunculated HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
1
19
0
2
Order By: Relevance
“…29 There are just as many reports in which HCC is described as growing extrahepatically, but the origin of HCC is not clearly identified. Such articles were excluded, because right-sided pedunculated HCC growing extrahepatically is often a fusion of metastatic adrenal HCC and the liver, 30 or HCC could have arisen in the liver and grown mainly extrahepatically. According to Yamashita et al, 9 there were 70 cases of ectopic liver reported in the literature up to 1985; they included 9 cases of HCC evolving in ectopic liver tissue.…”
Section: Casementioning
confidence: 99%
“…29 There are just as many reports in which HCC is described as growing extrahepatically, but the origin of HCC is not clearly identified. Such articles were excluded, because right-sided pedunculated HCC growing extrahepatically is often a fusion of metastatic adrenal HCC and the liver, 30 or HCC could have arisen in the liver and grown mainly extrahepatically. According to Yamashita et al, 9 there were 70 cases of ectopic liver reported in the literature up to 1985; they included 9 cases of HCC evolving in ectopic liver tissue.…”
Section: Casementioning
confidence: 99%
“…The right adrenal is most often involved while bilateral involvement is uncommon. The route for metastasis is thought to be hematogenous, but there is also a possibility of direct invasion (10). Metastasis is often diagnosed incidentally by routine abdominal imaging.…”
Section: Discussionmentioning
confidence: 99%
“…La plupart des carcinomes hépatocellu-laires décrits ont été découverts devant une masse abdominale [4,11,17,18] et simulent souvent une tumeur surrénalienne droite. [9,10]. L'examen physique retrouve souvent une masse abdominale de localisation variable.…”
Section: Commentairesunclassified